Taking Flight: Narratives, Logistics, and Risks of Chemsex Scenes in the Philippines - Lasco, Gideon (Archīum Ateneo, 2023)
Chemsex – the use of specific; illicit substances to facilitate and enhance sexual encounters – has been documented extensively across the Global North using qualitative methodologies. Elsewhere; however; little is known about the phenomenon. Our article addresses this gap in the scholarly literature by exploring how chemsex encounters transpire in the Philippines. Through semi-structured interviews; we demonstrate the spatiotemporal nature of chemsex scenes; showing how people move between physical and virtual domains across time as they find sexual partners; procure drugs; and organize and attend the actual encounter. Consequently; the risks faced by chemsex practitioners – to health and to security – are also spatiotemporally plotted within intersecting physical and virtual risk environments; and best mitigated by a form of experiential expertise that is likewise temporally determined. Ultimately; chemsex scenes in the Philippines are distinguished from the rest of the world by the state-led “war on drugs.” We consider our findings in the context of this war; showing how its very real and often fatal threats have shaped the way people navigate chemsex scenes and mitigate the risks through “counterpublic health” measures; and how its prominent ideologies and discourses are reflected in the ways by which people make sense of their drug use.